Penegakan Hukum terhadap Penerbitan Sertifikat Hak Pakai yang Tumpang Tindih dengan Sertifikat Hak Milik - Ghea Cindy Denata (Uniku Law Review, 2025)
The purpose of this study is to provide a legal analysis of the Bandung State Administrative Court Decision Number 84/G/2023/PTUN.BDG relating to a land dispute between the Plaintiffs as holders of Land Ownership Certificate No. 3546/Cikutra and the Bandung City Land Office regarding the issuance of Land Use Certificate No. 00215/Cikutra on behalf of the Bandung City Government. This study uses a case study method with a qualitative approach based on secondary data sourced from the PTUN decision, laws and regulations, and other supporting information. The results show that the panel of judges declared the object of dispute invalid and ordered the defendant to revoke the certificate due to administrative errors found, particularly in the measurement stage, verification of physical and legal data, and inconsistencies in the announcement procedure that resulted in overlapping with previously registered land rights. The conclusion of this study is that the process of issuing the Land Use Certificate does not comply with applicable land registration provisions and does not reflect the principles of land administration that guarantee legal certainty, prudence, and protection of the rights of legitimate landholders.